PEMBUATAN ECO ENZYME DAN POC DENGAN MEMANFAATKAN SAMPAH RUMAH TANGGA ORGANIK MENUJU ZERO WASTE - Arbiwati, Dyah; AZ, Abdul Rizal; Sandhi, Indah Kartika; Al Rosyid, Ali Hasyim (Dharma: Jurnal Pengabdian Masyarakat, 2023)
According to data from the Kementerian Lingkungan Hidup dan Kehutanan (2022), waste production in Indonesia is around 36 million tons per year and unmanaged waste is around 13.5 tons per year (37.45%). Waste production in Daerah Istimewa Yogyakarta is around 800 thousand tons per year, and  50.17% of it is household waste. The total volume of waste brought to the Piyungan landfill is around 700 tons/day, around 55 percent of it is organic waste. Each person produces around 0.68 kg of waste per day, so waste management must be the responsibility of all people communities as waste producers. The aim of community service activity is to increase knowledge, skills and motivate also raise awareness of KWT Cabe Rawit members in Jambon Village as partners in processing household waste into eco enzyme and Liquid Organic Fertilizer using the stacked bucket technique, so that it can support the zero waste movement. The implementation methods in community service activities including lectures, training and practice. The outputs that will be produced are publications in national seminar proceedings with ISBN, publications in electronic mass media, books with ISBN, videos, posters and increasing partner empowerment. All members of the KWT Cabe Rawit members in Jambon Village understand and are skilled in making eco enzymes and Liquid Organic Fertilizer from organic household waste and their benefits. The quality of Liquid Organic Fertilizer using the stacked bucket technique is an organic C content of 2.76%, 0.14% total N, C/ N 19.71, P2O5 0.0041 %, K2O 0.023% and pH 5.7. The quality of compost using the stacked bucket technique is organic C content 42.26%, total N 3.67%, C/N 11.51, P2O5 0.39%, K2O 0.17% and pH 6.2 and pH eco enzyme 3 .5Keywords: Eco enzyme, Household waste, Liquid organic fertilizer, Zero waste